Structure–Activity Relationship of Formamides as Organocatalysts: The Significance of Formamide Structure and Conformation. Issue 12 (7th March 2013) - Nguyen, Dieu; Akhani, Ravish K.; Sheppard, Cody I.; Wiskur, Sheryl L.
Abstract: The impact of the structure and conformation of formamides as organocatalysts was investigated and reported herein as a structure–activity relationship. Selected formamides and some amides were evaluated for their ability to activate allyltrichlorosilane in the allylation of benzaldehyde. The results suggest that the reactive conformation of secondary formamides is the less‐favorable cis conformation, whereas tertiary formamides and most amides are less reactive or unreactive in the reaction. A trend is observed between the Charton value for the N ‐substituent on the secondary formamides and the amount of product formed, with an increase in yield as the substituent becomes larger. This work highlights the effects of sterics and solvent polarity on the reactivity of formamides. Abstract : A structure–activity relationship with regard to formamides as organocatalysts is explored. This study highlights that the cis conformation of secondary formamides is the reactive conformation in the allylation of aldehydes with allyltrichlorosilane. Therefore, conditions that promote an increase in the cis conformation result in greater amounts of product formed.